2020
DOI: 10.21203/rs.3.rs-17917/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piper sarmentosum extract alleviates inflammatory responses and improves barrier function in porcine intestinal epithelial (IPEC-J2) cells induced by lipopolysaccharide (LPS)

Abstract: Background: In this study, we investigated the anti-inflammatory effect of Piper sarmentosum extract (PSE) in the IPEC-J2 cells induced by lipopolysaccharide (LPS). Meanwhile, we also tested the metabolomics profile of cells treated by LPS and PSE.Method: IPEC-J2 cells (6×10 5 cell/well) were seeded on 6-well plates, and cells were divided into three treatments (control, LPS treatment and LPS + PSE-NB treatment). Each treatment was conducted in five replicates. After incubation for 24 h, cells in LPS + PSE-NB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…They discovered that inhibiting gastric acid sufficiently with omeprazole prevented both ulcer recurrence and responses, indicating that acid may enhance gastric mucosal inflammation in response to IL-1β stimulation, resulting in gastric ulcers. Metabolic pathway analysis indicated that P. sarmentosum exerts anti-inflammatory activity mainly by affecting tryptophan metabolism ( Wang et al, 2020 ). Its metabolic product, melatonin, has anti-inflammatory properties by inhibiting the activation of nuclear factor kappa-light-chain-enhancer of activated B cells ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that inhibiting gastric acid sufficiently with omeprazole prevented both ulcer recurrence and responses, indicating that acid may enhance gastric mucosal inflammation in response to IL-1β stimulation, resulting in gastric ulcers. Metabolic pathway analysis indicated that P. sarmentosum exerts anti-inflammatory activity mainly by affecting tryptophan metabolism ( Wang et al, 2020 ). Its metabolic product, melatonin, has anti-inflammatory properties by inhibiting the activation of nuclear factor kappa-light-chain-enhancer of activated B cells ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic pathway analysis indicated that P. sarmentosum exerts anti-inflammatory activity mainly by affecting tryptophan metabolism ( Wang et al, 2020 ). Its metabolic product, melatonin, has anti-inflammatory properties by inhibiting the activation of nuclear factor kappa-light-chain-enhancer of activated B cells ( Wang et al, 2020 ). These findings are consistent with our results showing P. sarmentosum ’s anti-inflammatory activity on the inflammatory signaling pathway by downregulating IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%